A descriptive study on the coping strategies of parents of children with autism spectrum disorder in Tacloban City. - Dolina, Athena Lynn P.; Manarang, Charles Vincent C.; Pulma, Mariesan R. (Athena Lynn P. Dolina, 2012)
Although several studies about autism have been conducted worldwide, only a few of the said studies focused on the coping strategies of parents of children with Autism Spectrum Disorder (ASD). And only a minority of these focused on parents in Asian countries. This research is a qualitative and quantitative study of the coping strategies of parents with ASD in Tacloban City, which specifically seeks to (1) determine the different factors that result in stress of parents of children with ASD, (2) measure the level of stress of parents of children with ASD, and (3) identify the different coping strategies of parents whose children have ASD. The sample for this study consisted of 8 parents (6 mothers and 2 fathers) of children with ASD. The responses from the interviews generated data about the stresses that they encountered and their coping strategies. The level of stress of parents was measured using a subscale of the Family Impact Questionnaire (FIQ). Other tests such as the Sense of Coherence Scale (SOC) and Purpose in Life Test (PIL-R) measured the meaningfullness of the individual's lives. The results of these tests were used to support the level of stress present among parents. This research aims to guide parents' on how they can deal with the stresses tha they encounter in dealing with the stresses that they encounter in dealing with their child with ASD.